A Tool Supporting Production Planning in The Supply Chain – A Case Study of a Bus Manufacturer - michal JAKUBIAK (Communications of International Proceedings, 2024)
The increasing demands of customers, coupled with the persistent pressure to reduce costs and accelerate service delivery times, have elevated the importance of planning functions and forecasting future events. Through a review of selected literature, the author highlights various aspects of supply chain planning. The concept of advanced supply chain planning is presented, along with the limitations and challenges faced by managers responsible for the flow of products and information. The paper also addresses the role of Sales and Operations Planning (S&OP) in contemporary supply chain planning. Based on a real case study of entities collaborating within the automotive supply chain, the author develops an algorithm that aids in production planning and business decision-making in this area. This approach has been programmed and successfully supports the daily work of planners.
Keywords: Production Planning; Supply Chain; S&OP (Sales and Operations Planning)